Introgression of the Saltol into AS996, the elite variety of Vietnam, using Marker Assisted Backcrossing - Huyen, Luu Thi Ngoc; Cuc, Luu Minh; Abdelbagi, M. Ismail; Ham, Le Huy (VNU Journal of Science: Natural Sciences and Technology, 2012)
Abstract. This study focus on developing new salinity tolerance and high yielding rice lines, using markers assisted backrossing (MABC) as a technological tool for breeding. Total of 500 SSR markers on 12 rice chromosomes were screened for parental polymorphic markers. Of which, 52 primers in the Saltol region were examined with the two parents varieties to identify polymorphic primers for screening the Saltol region of the breeding populations. An analysis of 63 SSR markers on approx. 500 plants for each backcross generation of ASS996/FL478 for three steps selection. The two BC 1 F 1 plants P284 and P307 which had the highest  recipient alleles up to 89.06% and 86.36%, were chosen for the next backcrossing. Three BC 2 F 1 plants with the recipient alleles up to 94,03 and 93,18% were used to develop BC 3 F 1 generation. The best BC 3 F 1 plant was P284-112-209 with all the recipient alleles and Saltol region. The four plants P307-305- 21, P284-112-195, P284-112-198, P284-112-213 were the second ranking with only one locus heterozygous (applied 63 markers covere on 12 chromosomes). These five plants were chosen as the breeding lines as the result of Saltol -AS996 introgression. The breeding line BC 4 F 1 having 100% genetic background of donor variety is ready for develop new salinity tolerant variety ASS996-Saltol to cope with climate change. Keywords: AS996, marker assisted backcrossing, rice, Saltol , QTL.